Personal Growth Initiative sebagai Prediktor terhadap Prokrastinasi Akademik pada Mahasiswa - Susiswilujeng, Ridha Pradipta; Saraswati, Putri (Jurnal Psikologi Perseptual, 2023)
Students are the generation who can be said to be national assets because students are an educated group of people who are expected to be able to face various changes and existing problems. However, the facts show that various obstacles can be experienced by students when studying at university which can trigger student delays in completing their education or not graduating on time which will lead to academic procrastination. One of the factors that influence the level of academic procrastination in students is personal growth initiative. This is because personal growth initiative are closely related to efforts to develop someone in a positive direction by deliberately optimizing someone's potential to change to become a better person. Therefore, this study aims to test whether personal growth initiatives have a role so that they can be used as a solution to overcome the problems of academic procrastination experienced by students. The subjects of this were 334 male and female students who experienced academic procrastination. The measuring tool for both variables uses a Likert scale. The sampling technique used purposive sampling. The results of this study indicate that there is a negative influence between the personal growth initiative variable (x) and the academic procrastination variable (y) with the simple linear regression equation Y = 56,548 + (- 0,283)*X. Berbagai kendala bisa saja dialami oleh mahasiswa ketika menempuh pendidikan di perguruan tinggi, yang akhirnya menjadi pemicu keterlambatan penyelesaian pendidikan mahasiswa, salah satu faktor penyebabnya adalah prokrastinasi akademik yaitu menunda-nunda pekerjaan. Demikian juga prokrastinasi akademik dapat dipengaruhi oleh personal growth initiative yang berkaitan erat dengan usaha-usaha untuk mengembangkan diri ke arah yang positif dengan mengoptimalkan potensi dirinya secara sengaja untuk terus berubah menjadi pribadi yang lebih baik. Oleh karenanya, penelitian ini bertujuan untuk menguji apakah personal growth initiative memiliki peran sehingga dapat dijadikan sebagai solusi untuk mengatasi permasalahan prokrastinasi akademik yang dialami oleh mahasiswa. Teknik pengambilan sampel dengan purposive sampling, maka sebanyak 334 mahasiswa yang teridentifikasi mengalami prokrastinasi akademik terlibat dalam penelitian ini. Instrumen yang digunakan adalah skala personal growth initiative dan skala prokrastinasi akademik. Analisis data menggunakan Jamovi. Hasilnya menunjukkan bahwa terdapat pengaruh negatif antara variabel personal growth initiative (x) dengan variabel prokrastinasi akademik (y) dengan persamaan regresi linier sederhana Y = 56.548 + (- 0.283)*X.